Rapid identification of unknown pathogens in environmental samples using a high-throughput sequencing-based approach. Issue 5 (May 2019) - Israeli, Ofir; Cohen-Gihon, Inbar; Zvi, Anat; Lazar, Shirley; Shifman, Ohad; Levy, Haim; Tidhar, Avital; Beth-Din, Adi
Abstract: In the event of a bioterror attack, a prompt, sensitive and definite identification of the agents involved is of major concern for confirmation of the event and for mitigation of countermeasures. Whether the information from intelligence forces is limited concerning the biothreat identity or one suspects the presence of a novel or engineered agent, the genetic identification of microorganisms in an unknown sample is challenging. High-throughput sequencing (HTS) technologies can sequence a heterogeneous mixture of genetic materials with high sensitivity and speed; nevertheless, despite the enormous advantages of HTS, all previous reports have analyzed unknown samples in a timeframe of a few days to a few weeks. This timeframe might not be relevant to an emergency scenario. Here, we present an HTS-based approach for deciphering the genetic composition of unknown samples within a working day. This outcome is accomplished by a rapid library preparation procedure, short-length sequencing and a prompt bioinformatics comparison against all available microbial genomic sequences. Using this approach, as a proof of concept, we were able to detect two spiked-in biothreat agents, B. anthracis and Y. pestis, in a variety of environmental samples at relevant concentrations and within a short timeframe of eight hours.